O agro-hidronegócio no Vale do São Francisco : território de produção de riqueza e subtração da riqueza da produção - Sousa, Raimunda áurea de (2013)
It is verified in this thesis: to be the nature of capital strength extraction of surplus labor makes borderless. To this end, international competitiveness and efficiency productivist guide the European Common Agricultural Policy evading wealth polo Juazeiro/ Petrolina, in that obtains control of the land, water and all stages of production in the field by imposing stamp certifications as a determinant of the free movement of goods in the European market. Centered in the rules of accumulation and exploitation of the system capital, agro-hydro expands supported and encouraged by the state, as the only way to raise the standard of living of workers in town and country, justified the quantitative employment generated, which in turn, can result in unnecessary consumption of the city. While this discourse is divulgadado, land and water become appropriated by the owners of capital specifically for crop production required by the international market. Thus, demand for tropical fruits by countries that comprise the European Union has allowed the PAC to exert its total domination in the Valley, determining how to behave employee and employer, without necessarily having title to the land. Thus, the irrigation policy in areas that were implanted with the irrigated areas in particular: Bebedouro Nilo Coelho and Salitre has actually expanded production quantitatively and qualitatively, but this apparently positive balance has been extracted from the land rent , materialized in the precarious and temporary employees as well as the monopolization of land of small farmers who still has nominal bond with it. It is therefore the mediation of this land in the center of the factors that promote the separation between the place of production of the means of life that does not take the form of variable capital necessary reproduction of the worker and the place of production and reproduction of capital. With this, the surplus labor time that capital appropriates is shared by many capitalist agents in Polo and Europe.